Coexistence of CADASIL and Alzheimer's disease. Issue 6 (1st June 2003) - Thijs, V; Robberecht, W; De Vos, R; Sciot, R
Abstract : Cerebral autosomal dominant arteriopathy with subcortical infarcts and leucoencephalopathy (CADASIL) is caused by point mutations in the Notch3 gene. Presenilins are proteins involved in the cleaving of both Notch and the amyloid precursor protein (APP). In cases of early onset Alzheimer's disease mutations of the presenilin genes (PSEN 1 and PSEN 2) and APP can be found. A 64 year old patient with CADASIL (R169C-mutation) is reported, who, in addition to subcortical infarcts and granular osmiophilic deposits, had numerous senile plaques and neurofibrillary tangles on pathological examination. Mutations in the APP, PSEN1, and PSEN2 genes were not identified. Neuropathological findings of Alzheimer's disease may be found in CADASIL patients.